Optofluidic Tunable Linear Narrow-Band Filter Based on Bragg Nanocavity - Chaolong Fang; Bo Dai; Qiao Xu; Qi Wang; Dawei Zhang (IEEE Photonics Journal)
A compact, tunable linear optofluidic Bragg filter is simulated, designed, fabricated, and characterized. The device consists of a nanocavity sandwiched by two symmetrical film stacks made of high- and low-refractive-index dielectric materials. The fabrication parameters are simulated by using the commercial software Essentical Macleod. The resonant wavelength can be linearly shifted by up to 34.8 nm when the refractive index of the liquid injected into the Bragg nanocavity varies from 1.333 to 1.51. Meanwhile, the filter has a narrow bandwidth of 1.1 nm and a very high extinction ratio of –20.2 dB with the sensitivity (Δλ/Δn ) of 374 nm/RIU.